2009
DOI: 10.1089/jpm.2008.0285
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Evaluation of a Pediatric Palliative Care Educational Workshop for Oncology Fellows

Abstract: Although perceived competence and comfort with palliative care improved, the workshop did not uniformly produce lasting improvements in knowledge. Sustained knowledge will likely require more intensive training in palliative care. Continued research and evaluation of similar educational programs are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Recently, interventions and educational initiatives have aimed to improve medical communication, 34-36 but many healthcare providers still report they do not feel adequately prepared to give bad news, discuss end-of-life issues, or have conversations about sensitive topics with families. 8, 37 Hence, these areas of communication remain important topics for future research and clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, interventions and educational initiatives have aimed to improve medical communication, 34-36 but many healthcare providers still report they do not feel adequately prepared to give bad news, discuss end-of-life issues, or have conversations about sensitive topics with families. 8, 37 Hence, these areas of communication remain important topics for future research and clinical care.…”
Section: Discussionmentioning
confidence: 99%
“…Our research has confirmed that oncologists are not well-trained to have these difficult EOL conversations, and ongoing education is needed to sustain knowledge of palliative care (Baughcum, Gerhardt, Young-Saleme, Stefanik, & Klopfenstein, 2007;Gerhardt et al, 2009). As a result, referrals to palliative care or hospice often occur late in the disease process or not at all.…”
Section: Mid-career: Pearl 5-network and Collaboratementioning
confidence: 58%
“…Of the total 97 articles on pediatric palliative care, there were 55 articles on clinicalpractice,[202229333540424450525355575960636870747577808183869295100103106110,112113] 8 articles on education,[30697376878890114] 7 articles on research,[2428435661104105] and 27 articles on administration. [212325273132344151545862717278798289919394101102111115116] The relative reporting prevalence for the four categories is provided in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…[2236384447495355678186929596109] There were six original articles[6973768790114] and two review articles[3088] among the eight articles on education, and two original articles,[56] and six review articles[24284361104105] among seven articles on research, respectively. Of the 27 articles on administration, there were 15 original articles[212358717278798294101102111115116] and 12 review articles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation